GAMBARAN SPIRITUALITAS REMAJA YANG TINGGAL DI SEKITAR EKS-LOKALISASI - Yusuf, Ah.; Tristiana, Rr Dian; Agustina, Nina (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
Spirituality is one of the most influential dimensions in adolescent development. Adolescent with good spiritual sees life with optimism, clean mind and soul. Environment will affect the spiritual development of adolescents. This research aimed to understanding the adolescent spirituality living around ex-localization. This research used qualitative research design of phenomenology with in-depth interview with semi structured interview and observation. Participants were junior high school teenagers, Moslems living around exlocalization, Kota Surabaya, choose by purpossive sampling. The data analysis in this study using thematic analysis with nine steps Collaizzi. result of this research got 18 theme that is adolescent perception, adolescent behavior, adolescent relationship with parents, interaction of adolescent with society, interaction of adolescent with opposite sex, adolescent knowledge, adolescent relationship with self, autonomy, feeling during worship, SWT, the purpose of human creation, religious analysis, Allah's incomprehension, the timeliness of worship, obstacles, life goals, hopes, spiritual experiences, ways of dealing with problems, lifestyles, self-image. Adolescents who live in an ex-localization will interact with peers and the surrounding community in the neighborhood. These reciprocal relationships affect the spiritual values in teenagers. The existence of the control of parents can control the interaction process that occurs between adolescents with the surrounding community who live in ex-localization so that formed the spiritual character of adolescents.